Critical Close Reading Model Design Assisted by Visible Thinking Routines to Strengthen Students' Literary Analysis Abilities - Lutfi Syauki Faznur; Didah Nurhamidah; Choirul Asari (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
Literary learning in higher education still tends to take place at an appreciative and descriptive level so that student analysis often stops at thesummary of the content, mention of intrinsic elements, and personal impressions of the text. This research aims to design and test the feasibilityand effectiveness of the Critical Close Reading model assisted by Visible Thinking Routines to strengthen students' literary analysis skills in thePoetry Studies course. The research uses a mixed methods approach with an exploratory sequential design. The subject of the study is a student ofthe Indonesian Language and Literature Education Study Program, University of Muhammadiyah Jakarta who took the Poetry Studies course.Data were collected through observations, interviews, questionnaires, documentation, expert validation, Visible Thinking Routines worksheets,and literature analysis ability tests. Qualitative data were analyzed through reduction, presentation, and conclusion drawn, while quantitative data were analyzed using percentages, normality tests, paired sample t-tests, and N-Gain. The results of the study show that the developed modelhas a systematic syntax, including reading the text closely, observing textual patterns, asking critical questions, drafting interpretive claims,supporting claims with textual evidence, connecting texts with context, revising arguments, and reflecting understanding. Expert validation showsthe model is in the very feasible category. The application test showed an increase in the average pretest from 61.32 to 82.15 in the posttest withan N-Gain of 0.54 in the medium category. Qualitatively, student analysis shifts from a descriptive pattern to a more argumentative pattern, basedon claims, evidence, reason, and reflection. Thus, this model is suitable to be used as an alternative to learning Poetry Studies that is morecritical, systematic, and textual evidence-based.